The part of justices of the peace in establishing of the English navy in the late 16th – early 17th centuries (by the materials of Norfolk county) - Vladimir P. Mitrofanov (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки, 2023)
Background. The activity of justices of the peace as authorities in the counties of England during the Tudors and the first Stuarts, although considered by historians, have not yet been studied, which is noted in the research. By the materials of Nathaniel Bacon, who was the justice of the peace of the Norfolk county, one of the little-studied aspects of the activity of justices of the peace is considered, namely their part in the formation of marine crews for the Royal Navy. Materials and methods. Using the case-studies method, observing the principle of historicism, and the method of analysis and synthesis, various documentary and narrative sources available in the collection of N. Bacon fore the period 1580–1620 are analyzed. Results. An analysis of the sources showed the degree of participation of the justiceof the peace N. Bacon in the recruitment of sailors in the fifteen hundred of Norfolk county at the end of the 16th century and in 1620. His financial expenses fore these purposes and some other administrative actions are noted. The quantitative and personal date of people recruited into the Royal Navy are also determined. Conclusions. In addition to his participation in the socio-economic issue of local life, N. Bacon Was directly involved in the recruitment of sailors for the Royal Navy, using state’s funds. It was an episodic activity, but it required the justice of peace to personally visit the towns and villages of the county, accounting for state’s funds, maintaining contacts with both the constables of the hundreds and the officials of the Crown. The royal authority was pleased with his work in this regard. Without the participation of justices of peace, it is unlikely that officials of maritime department would be able to quickly recruit marine crews.